2013
DOI: 10.1177/0956797612472343
|View full text |Cite
|
Sign up to set email alerts
|

The Harm-Made Mind

Abstract: People often think that something must have a mind to be part of a moral interaction. However, the present research suggests that minds do not create morality but that morality creates minds. In four experiments, we found that observing intentional harm to an unconscious entity--a vegetative patient, a robot, or a corpse--leads to augmented attribution of mind to that entity. A fifth experiment reconciled these results with extant research on dehumanization by showing that observing the victimization of consci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 22 publications
(21 reference statements)
7
44
2
1
Order By: Relevance
“…The present study extended the findings of Ward et al [5] in three ways. First, although the dyadic moral template is assumed to consist of two parties—an agent and a patient—regardless of whether the agent takes a morally good or bad action, Ward and colleagues only investigated the effect of an immoral act (i.e., harming the robot).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study extended the findings of Ward et al [5] in three ways. First, although the dyadic moral template is assumed to consist of two parties—an agent and a patient—regardless of whether the agent takes a morally good or bad action, Ward and colleagues only investigated the effect of an immoral act (i.e., harming the robot).…”
Section: Introductionsupporting
confidence: 89%
“…Mind perception can be increased when the entity is involved in moral acts, even if the entity is usually thought to be mindless [5]. Ward and colleagues conducted vignette experiments and showed that participants tended to attribute more mind, specifically, the capacity to experience pain, to a robot when it is harmed than when treated appropriately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People can fail to see harm in cases of genocide (Castano & Giner-Sorolla, 2006;Jahoda, 1998), child slavery (Gomey, 2011), or torture (Gray & Wegner, 2010b;Greenberg & Dratel, 2005) simply by stripping others of mind (Bandura, Barbaranelli, Caprara, & Pastorelli, 1996;Haslam, 2006). Conversely, people can see harm in appar ently victimless acts by ascribing more mind to animals (Bastian, Costello, Loughnan, & Hodson, 2012), fetuses (Gray, Gray, & Wegner, 2007), nature (Tam, Lee, & Chao, 2013), vegetative patients (Gray, Knickman, & Wegner, 2011), and robots (Gray & Wegner, 2012;Ward, Olsen, & Wegner, 2013). Motivation can also alter perceived harm, as people strip minds from those they hate (Castano & Giner-Sorolla, 2006;Goff, Eberhardt, Williams, & Jackson, 2008;Haslam, 2006;Osofsky, Bandura, & Zimbardo, 2005) and confer them on those they love (Gardner & Knowles, 2008;Waytz, Gray, Epley, & Wegner, 2010).…”
Section: Moral Dumbfounding and Perceived Harmmentioning
confidence: 93%
“…People see victims or suffering in proportion to the severity or intentionality of various moral transgressions (DeScioli, 2008;DeScioli, Gilbert, & Kurzban, 2012;Gutierrez & Giner-Sorolla, 2007;Haidt & Hersh, 2001;Ward et al, 2013). For example, intentional harms are seen to cause more harm (Gray & Wegner, 2008) and to be overall worse than unintentional harms (Ames & Fiske, 2013).…”
Section: Moral Dyad and Dyadic Completionmentioning
confidence: 96%